2000
DOI: 10.1099/00221287-146-8-1933
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Lys-gingipain protease activity in Porphyromonas gingivalis W50 is independent of Arg-gingipain protease activities

Abstract: Porphyromonas gingivalis, a black-pigmenting anaerobe implicated in the aetiology of periodontal disease, contains two loci, rgpA and rgpB, encoding the extracellular Arg-X specific proteases (RGPs, Arg-gingipains), and kgp, which encodes a Lys-X specific protease (KGP, Lys-gingipain). The rgpA and kgp genes encode polyproteins comprising pro-peptide and catalytic domain with large N-and C-terminal extensions which require proteolytic processing at several Arg and Lys residues to generate mature enzymes. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 37 publications
8
55
0
1
Order By: Relevance
“…It was found that leupeptin inhibited the cleavage of all substrates, except for BikKam14, the only substrate in which no arginine residue is present (Table 4). This finding is in agreement with findings by Aduse-Opoku and coworkers, who observed inhibition of Arg-gingipain activity in the presence of leupeptin, whereas no effect on Lys-gingipain activity was observed (1). A literature search revealed that the amidolytic activity of both Argand Lys-gingipain on L-BApNA is stimulated by the addition of glycyl-glycine (5, 7).…”
Section: Figsupporting
confidence: 82%
See 1 more Smart Citation
“…It was found that leupeptin inhibited the cleavage of all substrates, except for BikKam14, the only substrate in which no arginine residue is present (Table 4). This finding is in agreement with findings by Aduse-Opoku and coworkers, who observed inhibition of Arg-gingipain activity in the presence of leupeptin, whereas no effect on Lys-gingipain activity was observed (1). A literature search revealed that the amidolytic activity of both Argand Lys-gingipain on L-BApNA is stimulated by the addition of glycyl-glycine (5, 7).…”
Section: Figsupporting
confidence: 82%
“…1). In addition to the absence of Arg-gingipain in ⌬Rgp, it is known that ⌬Rgp strains secrete Lys-gingipain less efficiently (1,41). This was confirmed by the decreased proteolytic activity of ⌬Rgp culture supernatant on the BikKam14 substrate (Fig.…”
Section: Figmentioning
confidence: 54%
“…or 1i10"" c.f.u. of P. gingivalis W50, the isogenic luxS mutant or the kgp mutant K1A (Aduse-Opoku et al, 2000). K1A is known to be attenuated in this animal model (M. A. Curtis, unpublished data).…”
Section: N a Burgess And Othersmentioning
confidence: 99%
“…53978) and the mutant W50 strain K1A (kgp : :erm), lacking the Lys-Xaaspecific proteinase Kgp [19], were obtained from the culture collection of the School of Dental Science, The University of Melbourne. Strains W50, K1A and W50AB (see below) were grown anaerobically and maintained ( 10 passages) on horse blood agar (HBA ; Oxoid Blood Agar Base 2, Oxoid, Basingstoke, U.K.) supplemented with 10 % (v\v) defibrinated horse blood, with weekly subculturing.…”
Section: Bacterial Strains and Batch Culture Growth Conditionsmentioning
confidence: 99%
“…The residue preceding the N-terminus of most of the domains is arginine, suggesting the involvement of the arginine-specific proteinases, RgpA and RgpB, in N-terminal processing. To investigate the involvement of these enzymes in N-and Cterminal processing, OMs were prepared from mutant strains lacking either a functional Kgp (K1A) [19] or both RgpA and RgpB in a double mutant (W50AB) that was constructed by insertional inactivation for this study. The correct insertion of the antibiotic-resistance cassettes into the rgpA and rgpB genes in W50AB was confirmed by Southern blot analysis (results not shown).…”
Section: Proteolytic Processing Of Rgpa Kgp and Hagamentioning
confidence: 99%